2021
DOI: 10.1021/acs.jpcc.1c06984
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Alkanethiolate and Aromatic Thiolate Self-Assembled Monolayers on Au(111): An X-ray Photoelectron Spectroscopy Study

Abstract: Applications of functional self-assembled monolayers (SAMs) rely to a large extent on their stability, with the thermal stability being of particular importance. In this context, thermal stability of archetypical, non-substituted alkanethiolate (AT) and aromatic thiolate (ArT) SAMs on gold was studied by synchrotron-based high-resolution X-ray photoelectron spectroscopy, taking several monolayers with different lengths of the molecular backbones as representative examples and heating them in UHV. Evaporated, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…49 This doublet is accompanied by a weak shoulder at a low BE, corresponding to an additional, weak doublet at ∼161.0 eV (S 2p 3/2 ), which can be assigned to atomically adsorbed sulfur, based on the results of thermal stability experiments. 50,51 The spectral weight of this latter doublet is, however, comparably small, so that the respective species can be considered as minor contamination only and it can be concluded that all molecules in the films are bound to the substrate via the thiolate anchor.…”
Section: Resultsmentioning
confidence: 99%
“…49 This doublet is accompanied by a weak shoulder at a low BE, corresponding to an additional, weak doublet at ∼161.0 eV (S 2p 3/2 ), which can be assigned to atomically adsorbed sulfur, based on the results of thermal stability experiments. 50,51 The spectral weight of this latter doublet is, however, comparably small, so that the respective species can be considered as minor contamination only and it can be concluded that all molecules in the films are bound to the substrate via the thiolate anchor.…”
Section: Resultsmentioning
confidence: 99%
“…The retention in the hydrophobic state permanently is extraordinary, though, taking into account previous reports. , Importantly, the collected water phase after the experiment was shaken with 2 mL of chloroform, and no coloration of the organic phase was observed. This indicates that the loss of the nanomaterial abilities was not caused by the detachment of DASA ligands from NPs but rather ligand degradation during the procedure. , …”
Section: Resultsmentioning
confidence: 88%
“…This indicates that the loss of the nanomaterial abilities was not caused by the detachment of DASA ligands from NPs 44 but rather ligand degradation during the procedure. 43,44 First, we investigated the photostability of compounds 5 and 4 (i.e., DASA-SAc and its immediate DASA-moiety-bearing substrate, respectively). We took about 2 mg of each compound and dissolved it in CHCl 3 (10 mL).…”
Section: Resultsmentioning
confidence: 99%
“…Thus where I S2 0 is the signal that would be expected in the absence of attenuation effects and λ org,S is the EAL of the organic matrix for the S 2p electrons. Following a recent publication by Asyuda et al, the thickness of the complete SAM can be related to that of the hydrocarbon layer by just adding to the latter the contribution from the S–Au interface ( t S ), as t SAM = t C + t S , taking t S = 0.24 nm (Scheme ). The quantity I S2 0 is expected to be proportional to the thiolate surface density: I S2 0 = K σ S N S2 / A , where N S2 is the number of thiolates in the excited area A , K is a constant, which involves several experimental parameters, and σ S is the photoemission cross section of sulfur.…”
Section: Methodsmentioning
confidence: 99%